Gestão de Ativos Industriais de uma Linha de Transporte de Paletes usando IIoT - David, Gabriel Augusto [UNESP]; Guarnetti, Rodrigo; de Oliveira, Gerson [UNESP]; Godoy, Eduardo Paciência [UNESP]; de Oliveira Conceição, Pedro [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
With the advent of the 4th Industrial Revolution and the emergence of the Industrial Internet of Things (IIoT), the integration of information from the industrial field became necessary to meet the demands of the competitive market that demands high efficiency and productivity from companies. The present study explores the implementation and operation of a maintenance supervision system on a pallet transport line based on IIoT. The proposed methodology allows the monitoring of representative data, such as vibrations and temperature, and the process information available in real time, allowing management and decision making based on indicators such as MTBF (Mean Time Between Failures) and MTTF (Mean Time To Failure), important indicators in the management of industrial assets. From the implementation of the proposed system, it was possible to obtain a broader view of the operation and vibrations of the monitored system, which made it possible to carry out a review in the maintenance plan seeking to identify potential process failures and decrease operating micro stops, therefore, contributing with a reliable solution for monitoring the systems of pallet transport lines using the concepts of Industry 4.0.
Keywords: Data science; Industrial asset management; Industrial internet of things; Industrial maintenance